2014
DOI: 10.1002/anie.201400176
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bonding Switches the Spin State of Diphenylcarbene from Triplet to Singlet

Abstract: Spin specificity is one of the most important properties of carbenes in their reactions. Alcohols are typically used to probe the reactive spin states of carbenes: O-H insertions are assumed to be characteristic of singlet states, whereas C-H insertions are typical for the triplets. Surprisingly, the experiments presented here suggest that the spin ground state of diphenylcarbene 1 switches from triplet to singlet if the carbene is allowed to interact with methanol. Carbene 1 and methanol form a strongly hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
102
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(122 citation statements)
references
References 21 publications
18
102
0
2
Order By: Relevance
“…When D 2 O was used in these experiments, the spectrum of this new species looked virtually identical, and none of its bands showed significant isotopic shifts. Recently, we reported that triplet diphenylcarbene T-8 reacted with both single molecules of CH 3 OH [18] and H 2 O [14] to form strongly hydrogen-bonded complexes between the singlet carbene S-8 and the hydrogen bond donors. We therefore assign the new species formed in the reaction between T-6 and H 2 O to the singlet carbene complex S-6···H 2 O.…”
mentioning
confidence: 99%
“…When D 2 O was used in these experiments, the spectrum of this new species looked virtually identical, and none of its bands showed significant isotopic shifts. Recently, we reported that triplet diphenylcarbene T-8 reacted with both single molecules of CH 3 OH [18] and H 2 O [14] to form strongly hydrogen-bonded complexes between the singlet carbene S-8 and the hydrogen bond donors. We therefore assign the new species formed in the reaction between T-6 and H 2 O to the singlet carbene complex S-6···H 2 O.…”
mentioning
confidence: 99%
“…The low-lying states of 1 A 1 (σ 2 π 0 ) and 1 B 1 (σ 1 π 1 ) are 10.4 and 33.1 kcal/mol [45][46][47][48][49] above the ground state, respectively (Schemes 2, 3).…”
Section: Electronic Structures Of Nhcmentioning
confidence: 99%
“…Diphenylcarbene 5 has been also studied in cryogenic matrices [25][26][27][28] and shown to be rather photostable under these conditions. In particular, prolonged broad band UV-visible irradiation of matrix-isolated 5 using a high-pressure mercury arc lamp did not lead to the expected ring opening to cyclohepatetraene 8.…”
Section: Introductionmentioning
confidence: 98%